Work–Family Interface as Mediator Between HRM Practices and OCB - Karisma Ilmiana; Nang Among Budiadi; Fidela Berliani Prasaja Putri (Penerbit Goodwood, 2025)
Purpose: This study explores the role of work–family interface (WFI) mediation in the relationship between human resource management (HRM) practices and organizational civic behavior (PKO). Methodology/approach: Using a quantitative survey approach, data was collected from 210 employees of PT Tri Usaha Sejahtera Pratama in Sragen Regency who were selected through cluster random sampling. The research instrument has been tested for validity and reliability (loading factor > 0.6; Composite Reliability > 0.7). The analysis was performed by simple and multiple linear regression to test four main hypotheses. Results/findings: The results showed that (1) MSDM practices had a positive and significant effect on PKO, (2) WFI had a significant positive effect on PKO, (3) MSDM practices had a significant positive effect on WFI, and (4) WFI partially mediated the relationship between MSDM practices and PKO. Conclusion: These findings confirm that HR policies that support work-family balance not only improve employee well-being, but also encourage the realization of extra-role behaviors that are crucial for organizational performance. Limitations: The main limitation of the study lies in the coverage of a single location and the cross-sectional design, so the generalization of the results needs to be done carefully. Contribution: Advanced research is recommended to expand the industry context, apply longitudinal design, and incorporate qualitative methods to understand the WFI mechanism more comprehensively.